The Effect of Application of Accounting Systems and Utilization of Information Technology on the Accountability of Village Fund Management (Case Study in Tanjunganom Village) - Eka Fitriana Aryanti; Khanifah Khanifah; Agus Triyani (International Journal of Management, Business, and Social Sciences, 2023)
This study was conducted with the aim of testing the effect of the Application of the Village Financial Accounting System Application and the Utilization of Information Technology on the Accountability of Village Fund Management in Tanjunganom Village. The population in this study is the village apparatus in Tanjunganom Village. This study uses a quantitative approach. Data was collected using a questionnaire with a sample of 32 respondents. This research was processed using SPSS version 24. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and t test (partial test). These results indicate that the Village Financial Accounting System Application has a positive effect on Village Fund Management Accountability, but Information Technology Utilization has no effect on Village Fund Management Accountability.